Připravenost podniků na vzdělávání zaměstnanců s využitím ICT – porovnání zemí Visegrádské čtyřky - Monika Volfová (Vydavatelství ZČU v Plzni, 2021)
The rapid growth and use of information and communication technology tools affect both private and business activities. In order to maintain their position, companies invest in their employees, especially in their lifelong training in the field of ICT skills development. This paper examines how companies from the Visegrad Four countries are prepared for employee training using ICT. The aim of the paper is to examine the extent to which companies in these countries provide training to develop or improve ICT skills, what is the level of digital skills in each country and what proportion of companies employ ICT specialists. At the end of the paper, a linear regression is performed to confirm or reject the positive relationship between the three variables – Human Capital, Use of Internet Services and data about enterprises that provide training in order to develop or upgrade the ICT skills of their employees. Data from Community survey on ICT usage in enterprises were collected from Eurostat. Data on the Digital Economy and Society Index (DESI) were collected for comparative analysis. The results suggest that there is no positive relationship between ICT employee training and indicator Human Capital from the DESI index but there is positive relationship between ICT employee training and indicator Use of Internet Services.